Developing Character Education with 4C Skills in Muhammadiyah Schools: Mengembangkan Pendidikan Karakter dengan Keterampilan 4C di Sekolah Muhammadiyah - Zativalen, Oriza; Irmaningrum, Rizka Novi; Wibowo, Teguh Hadi; Laili, Viviana Nisful (Pedagogia : Jurnal Pendidikan, 2025)
The intracurricular learning process tends to lack high character values, especially Al-Islam and Muhammadiyah characters at Muhammadiyah Elementary Schools. Students only focus on the learning process with knowledge output. Attitudes and skills are often forgotten in the teaching and learning process. Students have not yet installed the 4C skills (critical thinking, collaboration, communication, creativity). This research is to develop a character education model in the intracurricular learning process, namely the Al-Islam and Muhammadiyah character education model for Muhammadiyah elementary school students. The AIK character education model will be developed with 4C skills (critical thinking, collaboration, communication, creativity) as the latest outcome that 4C skills are able to help and develop students' AIK character in thinking creatively and facing problems. It is hoped that the AIK character model based on 4C skills will be able to score AIK character scores with 4C skills in the intracurricular learning process at Muhammadiyah elementary schools. Highlights: Integrating 4C skills into character education at Muhammadiyah schools. Developing moral values and competencies in students through the Al-Islam model. The model’s effectiveness proven by expert validation and student outcomes. Keywords: Character Building, 4C Competency, Al Islam Muhammadiyyah